Differential modulation of the lactisole 'Sweet Water Taste' by sweeteners. - Cynthia Alvarado; Danielle Nachtigal; Jay P Slack; Barry G Green (PLoS ONE, 2017)
Pre-exposure to taste stimuli and certain chemicals can cause water to have a taste. Here we studied further the 'sweet water taste' (SWT) perceived after exposure to the sweet taste inhibitor lactisole. Experiment 1 investigated an incidental observation that presenting lactisole in mixture with sucrose reduced the intensity of the SWT. The results confirmed this observation and also showed that rinsing with sucrose after lactisole could completely eliminate the SWT. The generalizability of these findings was investigated in experiment 2 by presenting 5 additional sweeteners before, during, or after exposure to lactisole. The results found with sucrose were replicated with fructose and cyclamate, but the 3 other sweeteners were less effective suppressors of the SWT, and the 2 sweeteners having the highest potency initially enhanced it. A third experiment investigated these interactions on the tongue tip and found that the lactisole SWT was perceived only when water was actively flowed across the tongue. The same experiment yielded evidence against the possibility that suppression of the SWT following exposure to sweeteners is an aftereffect of receptor activation while providing additional support for a role of sweetener potency. Collectively these results provide new evidence that complex inhibitory and excitatory interactions occur between lactisole and agonists of the sweet taste receptor TAS1R2-TAS1R3. Receptor mechanisms that may be responsible for these interactions are discussed in the context of the current model of the SWT and the possible contribution of allosteric modulation.